2023
DOI: 10.1021/acs.est.3c03170
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Polycyclic Aromatic Hydrocarbon Derivatives: Occurrences, Levels, Biotransformation, Exposure Biomarkers, and Toxicity

Bo Peng,
Qianli Dong,
Fangzhou Li
et al.

Abstract: Polycyclic aromatic hydrocarbon (PAH) derivatives constitute a significant class of emerging contaminants that have been ubiquitously detected in diverse environmental matrixes, with some even exhibiting higher toxicities than their corresponding parent PAHs. To date, compared with parent PAHs, fewer systematic summaries and reanalyses are available for PAH derivatives with great environmental concerns. This review summarizes the current knowledge on the chemical species, levels, biotransformation patterns, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 189 publications
0
9
0
Order By: Relevance
“…It should be noted that the risks of some PACs were not assessed because toxicity data were not available. Previous study reported that some SPAHs, such as 5-methylchryren, 7,12-benz­[ a ]­anthracenquinone 1,8-dinitropyrene, and 7-chlorobenz­[ a ]­anthracene, were much more mutagenic and carcinogenic than those of parent PAHs. Toxicities of these PACs should be further investigated for filling the knowledge and data gap and improving the risk management of PACs.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the risks of some PACs were not assessed because toxicity data were not available. Previous study reported that some SPAHs, such as 5-methylchryren, 7,12-benz­[ a ]­anthracenquinone 1,8-dinitropyrene, and 7-chlorobenz­[ a ]­anthracene, were much more mutagenic and carcinogenic than those of parent PAHs. Toxicities of these PACs should be further investigated for filling the knowledge and data gap and improving the risk management of PACs.…”
Section: Resultsmentioning
confidence: 99%
“…Humans are exposed to PAHs and their derivatives mainly through diet, inhalation, and dermal contact, and PAH derivatives are usually 10 to 1000 times more carcinogenic than the parent PAHs. 31,32 Some esters were also identified, and >30% of these esters were phthalates (PAEs). PAEs are endocrine disruptors and can also cause neurodevelopmental problems and hepatic toxicity.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Because they contain only benzene-the prototypical aromatic system-PBHs are sometimes considered the prototypical PASs and serve as model systems for investigating chemical concepts such as aromaticity 1 and reactivity. 2 In addition to their importance for fundamental studies, PBHs are pervasive in both the natural and man-made environments, and play key roles in multiple areas of research, including the formation of stars, 3-6 human health, 7 environmental impact, 8 andmore recently-as promising materials for organic electronics. 9 PASs in general, and PBHs in particular, have been used for a variety of electronic and optoelectronic technologies, including field effect transistors, [10][11][12][13][14] solar cells, 15 chemical sensors, 16 anode and cathode materials, [17][18][19][20][21] and anolytes 22 for redox-flow batteries.…”
Section: Introductionmentioning
confidence: 99%